Impact of the introduction of the modular written-theoretical examination in the training internship. - Mabel Rocha Vázquez; Mirtha A. Hernández López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Background: The formative process of teachers has always been a challenge due transformations undergone by educative institution's functions. Objective: To compare the results of modular examinations of two editions of the Professional Course. Methods: A analytic study was carried out to compare theoretical modular examinations results of Professional Course during 2003-2004 and 2004-2005 in which two different kind of test were used: oral and written, in that order. Universe and sample coincided and were represented by the totality of examined students. Data was collected from examination records and results were presented in tables of frequency expressed in percentage. Results: In a general way, quality index of 100% were obtained in every module during 2003-2004, contrary to 2004-2005 were any of the modules achieved 100%. The percentage of excellent marks was considerably higher using oral rather that written examination. The results distribution's curve is closer to the expected results using written examination; the results in municipalities and health areas are similar. Conclusion: The modular written examination allows a better selection of students being more effective in present conditions, with a young staff needing to be prepared.